(untitled) (Journal Of Educational and Psychological Researches, 2022)
Mental disorders (MDs) are a common problem in Primary Health Care Centers (PHCCs). Many people with serious MDs are challenged by symptoms and disabilities that result from the disease and by stereotypes and prejudice due to misconceptions about mental illness. This study aims at evaluating the knowledge, and attitude toward mental health concepts and services and causes of the reluctance to seek those services among people attending PHCCs. A descriptive cross-sectional study was conducted. The random sampling technique was used to include (10) of Directorates of Health (DoHs) coverage north, middle, and south of Iraq. The study was executed in (50) selected PHCs, (5) PHCCs in each DoH involved randomly selected (30) people attending the (50) selected PHCCs from (15) years old and above distributed equally in both genders. The total number of study participants was (1220) individuals. Data was collected through a self-assessment questionnaire. The Results revealed that The majority of people attending PHCCs believed that mental health is a fundamental aspect of human health. In return, half of them had frequent physical complaints without access to properly diagnose and management and did not know the existence of mental health services in PHCCs, more than two-thirds of people who suffer from mental health problems were not seeking for medical assistance, and about a quarter of them believe that mental disorders are madness. The research concluded that the knowledge and attitudes were still negative towards mental health. These calls for great efforts to spread community awareness towards different mental health concepts and raise the efficiency of medical and health staff to provide mental health services in PHCCs.